Optimization of agricultural biogas supply chains using artichoke byproducts in existing plants. (September 2018) - De Menna, Fabio; Malagnino, Remo Alessio; Vittuari, Matteo; Segrè, Andrea; Molari, Giovanni; Deligios, Paola A.; Solinas, Stefania; Ledda, Luigi
Abstract: The development of biogas production exacerbated the competition for land availability between crops dedicated to human consumption and those intended for energy production. Residual biomasses have been often proposed for their positive outcomes in terms of reduced pressure on land use. However, literature did not assess optimization options for existing biogas plants feeding. This paper developed a bio-economic model for the optimization of agricultural biogas supply chains using artichoke byproducts in existing plants. A multiple goal linear programming approach was adopted, using two objective functions, calculating respectively net present value and land use from energy crops, associated to a regional biogas network. Three scenarios were defined using primary and secondary data on the residues of a specific artichoke variety - globe - and an Italian region - Sardinia. In the Business As Usual scenario, net present value is about 7 million € with a land use of about 2720 ha. When using artichoke residues, the economic impact increases by 28% and land use is reduced by 83% if net present value is optimized. When land use is optimized, the economic impact still grows by 25% and land use is reduced by 100%. Results from this study confirm that, under certain conditions, locally available residual biomasses can replace energy crops in existing biogas networks, coupling viability and sustainability. Highlights: A bio-economic model for biogas optimization with byproducts (BioBO). Assessment of net present value and land use in 3 scenarios. Energy crops replacement with byproducts can couple viability and sustainability. BioBO model could be applied to other contexts and include other optimization goals.